Ubiór, strój i kostium w kontekście ubieralnej elektroniki (wearable electronic) - Gruchoła, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of the paper was an attempt to describe clothing of the wearable electronics domain, defined as smartmode, techmode, e-confection, equipment togs, dresstronics, electronic clothes or electronic fancy goods, constituing a symptom of the accomplishment of socio-cultural and technological transformation in the sphere of dress, attire and costume. Three questions were formulated in the research process: first, regarding the methodological status in the domain of wearable electronics; second, whether it is methodologically acceptable to define it as dress, attire or costume; third, which of the three afore-mentioned expressions may and ought to be used in referring to wearable electronics. The thesis was accepted that, despite semantic similarity, it is methodologically unwarranted to define clothing, which fulfils the function of dress, as wearable electronics. The thesis was confirmed. The historical and analytical descriptive methods were applied.